2011
DOI: 10.1128/cvi.00058-11
|View full text |Cite
|
Sign up to set email alerts
|

Induction of B Cell Responses upon Experimental Infection of Neonatal Calves with Mycobacterium avium subsp. paratuberculosis

Abstract: The objective of this study was to determine if experimental infection of neonatal calves with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…As reviewed by Chase et al (2008), IgM + B cells may comprise less than 5% of circulating lymphocytes, but early antigen encounters stimulate clonal expansion of this subset within weeks. Young calves that were experimentally infected intratonsillarly with MAP from 2 to 5 wk of age exhibited humoral reactivity to a ~50-kDa antigen of MAP (Waters et al, 2003), and calves exhibited B-cell responses to the pathogen by 3 mo of age (Stabel et al, 2011), demonstrating capabilities for early response. It is known that CD4 + and CD8 + T cells comprise about 20 and 10% of peripheral neonatal lymphocytes, respectively, and maintain a 2:1 ratio of relative abundance through adulthood (Chase et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reviewed by Chase et al (2008), IgM + B cells may comprise less than 5% of circulating lymphocytes, but early antigen encounters stimulate clonal expansion of this subset within weeks. Young calves that were experimentally infected intratonsillarly with MAP from 2 to 5 wk of age exhibited humoral reactivity to a ~50-kDa antigen of MAP (Waters et al, 2003), and calves exhibited B-cell responses to the pathogen by 3 mo of age (Stabel et al, 2011), demonstrating capabilities for early response. It is known that CD4 + and CD8 + T cells comprise about 20 and 10% of peripheral neonatal lymphocytes, respectively, and maintain a 2:1 ratio of relative abundance through adulthood (Chase et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The PBMC and mesenteric node lymphocytes (MNL) were cultured in replicate 48-well flat-bottomed plates (Nunc Technologies, Rochester, NY) at 39°C in 5% CO 2 in a humidified atmosphere. For each mononuclear cell sample, 1 plate was cultured for 24 h, 1 plate was cultured for 3 d, and 1 plate was cultured for 6 d. Duplicate wells were set up for each animal for each of the following in vitro treatments: medium alone [nonstimulated (NS)], concanavalin A (10 μg/ mL; Sigma, St. Louis, MO), pokeweed mitogen (10 μg/ mL; Sigma), and phytohemagglutinin (PHA; 10 μg/ mL; Sigma), or a whole-cell sonicate preparation of MAP (MPS; 10 μg/mL; Stabel et al, 2011). After 24 h, 1 set of plates was removed and centrifuged at 400 × g for 5 min.…”
Section: Isolation and Culture Of Peripheral Blood Mononuclear Cells mentioning
confidence: 99%
“…Previously, we observed that CD25 and CD26 expression was upregulated on T and B cells within 1 month after experimental infection of calves with M. avium subsp. paratuberculosis (27,28). Expression levels of both of these activation markers were also increased on CD4, CD8, and ␥␦ T cells after stimulation of PBMCs from M. bovis-infected cattle with either a recombinant early secretory antigenic target 6 and culture filtrate protein 10 fusion protein (rESAT-6:CFP-10) or M. bovis PPD (29).…”
Section: Discussionmentioning
confidence: 85%
“…CD26 also serves as a maturation marker for T cells, and its expression is highly correlated with Th1-mediated immunity and inflammation (29,30). Further, CD26 is linked with CD45 on the surface of T cells, resulting in the induction of T-cell signal transduction pathways (28,31). The expression of CD26 appears to be preferentially upregulated on CD4 ϩ CD45RO ϩ memory T cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about B cell contributions to immunity during M. avium subsp. paratuberculosis infections, it has been shown that B cells are highly activated in the early stages of infection, expressing CD5, a marker of antigen recognition (10,11). B cells also may become activated upon linkage of CD40 on the cell surface with CD40L present on activated T cells.…”
mentioning
confidence: 99%